2013
DOI: 10.3109/17483107.2013.806599
|View full text |Cite
|
Sign up to set email alerts
|

Crucial design issues for special access technology; a Delphi study

Abstract: Purpose. To develop and demonstrate a method to involve professional users of assistive technology (AT) in the development process of customisable products. Employing the ideas of user participation and mass customisation, this research addresses the need for reduced product costs and optimised product flexibility.Method. An adaptable six-question Delphi study was developed to establish consensus among AT professionals on design issues relating to a specified AT domain requiring innovation. The study is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…Although these results appear very encouraging, general statements about the strength and usability of the program will need to wait until new research has addressed the main limitations of the present study and determined the dependability of the data reported. New research efforts may also focus on modifying the technology used in this study (Ahmed et al 2015;O'Rourke et al 2014). In essence, one could try to concentrate all functions and applications in a single smartphone, resorting to the use of applications such as MacroDroid to facilitate task automation (Zhang et al 2016;Yadav 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although these results appear very encouraging, general statements about the strength and usability of the program will need to wait until new research has addressed the main limitations of the present study and determined the dependability of the data reported. New research efforts may also focus on modifying the technology used in this study (Ahmed et al 2015;O'Rourke et al 2014). In essence, one could try to concentrate all functions and applications in a single smartphone, resorting to the use of applications such as MacroDroid to facilitate task automation (Zhang et al 2016;Yadav 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers emphasized the benefit of identifying areas of disagreement through the use of Delphi (Snape et al, 2014 ; Tuominen, Tapio, Varho, Järvi, & Banister, 2014 ; Warth, von der Gracht, & Darkow, 2013 ). Other rationales provided can be broadly categorized as highlighting collaboration (Ferguson, Ireland, & Ireland, 2013 ; Munguatosha, Muyinda, & Lubega 2011 ; Nworie, 2011 ); structured group communication (Dikmen, Birgonul, Ozorhon, & Sapci, 2010 ; Keyvanfar et al, 2014 ; Manley & Zinser, 2012 ); the value of iteration and reflexivity (Ifinedo & Ifinedo, 2011 ; Loblaw et al, 2012 ; Venhorst, Zelle, Tromp, & Lauer, 2014 ); and greater democracy through anonymity (Chen, Wakeland, & Yu, 2012 ; O'Rourke et al, 2014 ; Venhorst et al, 2014 ). Only 19 articles were judged to provide some reference to a methodology, philosophy, or theoretical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the technology in real-life situations was clearly more challenging than its use in structured assessment contexts. Problems with device implementation are not unique to resource-limited environments [8]. However, lack of financial support for the acquisition of the system precluded the families from obtaining more integrated, robust, portable systems.…”
Section: Assistive Technologymentioning
confidence: 99%